Faktor Risiko Bayi Berat Badan Lahir Rendah di RS PKU Muhammadiyah Yogyakarta Tahun 2010 - Wira Septa; MTS Darmawan (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2011)
Birth weight was the most sensitif measurement tools and important to find out health baby status. birth weight baby less than 2.500 grams was included low birth weight infants. The proportion of low birth weight babies at 2000 - 2002 in Indonesia was about 9% (UNICEF, 2008). The aim of this study determine the risk factors that cause low birth weight babies (LBW). This research take 100 data from each respondent. The data consist of low birth weight babies (LBW) and infant birth weight enough (IBWE). Data collecting method in this research was using medical records. Data analysis technique used in this research were univariate and bivariate analysis with chi square test statistic (X2) at significant level α 5%. Results showed there was no significant relation between gender factor and low birth weight babies (LBW) (p = 0.256, RP = 0.85), there was significant relation between maternal parity status 1 and > 4 to the occurrence of LBW (p = 0.000, PR = 1.7) and there was significant relation between gestational age low birth weight (p = 0.000, PR = 3.37) which means that pregnancy was a risk factor for preterm low birth weight. Maternal parity and gestational age were a risk factor in low birth weight (LBW) but gender of babies was not risk factor in low birth weight (LBW).